FIXTURE LAYOUT DESIGN OPTIMIZATION USING SIMULATION SOFTWARE - TAUVIQIRRAHMAN (NIM : 231 04 007); Pembimbing : Dr. Ir. Yatna Yuwana M., MOHAMMAD
Fixture layout plays a vital role in machining accuracy. Traditionally, fixtures were designed by trial and error, which is expensive and time consuming. In this regard, researches based finite element analysis in fixturing has been widely applied by researchers. However, the primary drawback of these researchs is especially in modelling locator and clamp and machining operation. These researches consider the workpiece and the fixturing elements to be rigid, but however they are elastic and deformable. Cutting tool torque, which results in a trend of rotation of the workpiece, is not considered. The purpose of this research is to develop a method for modelling fixture elements and machining operation that accurately can predict workpiece deformation using the FEA based software. Knowledge of workpiece deformations induced by loading in a fixture-workpiece system is important to ensure quality part production. The FEA based software is used as tool for finding fixture element and machining operation modelling. The most representative modelling is treated as boundary conditions for optimizing fixture design process. ANSYS parametric design language code (APDL) is used to develop an algorithm to automatically optimize fixture layout, and clamping forces. Minimizing workpiece defomation is treated as an objective function in optimization of fixture layout design. The design variables in the optimization are locator and clamp positions, and clamping forces. The state variable is the von Mises effective stress and cannot exceed the yield strength of the workpiece. In this study, the finite element modellings were developed. These modellings consist of ; first, The element fixture modelling is more appropriate using surface contact. This modelling could predict workpiece deformations to within 3-5% of the experimental values. Second, it is appropriate to model cutting tool axial load with a single point load. Torque must be considered in the load model. The purpose of the optimization is to get a workpiece accuracy and stability in the same time. An algorithm of optimization written in the APDL code could succesfully optimize locators and clamps locations, and clamping forces automatically. This method could minimize workpiece deformations and clamping forces and reach the stability of the fixture-workpiece system.